2009
DOI: 10.1080/00288230909510498
|View full text |Cite
|
Sign up to set email alerts
|

Survival and retention ofEschenchia coliO157:H7 andCampylobacterin contrasting soils from the Toenepi catchment

Abstract: The effect of soil type on transfer of zoonotic bacteria to rural streams was investigated using intact cores and turfs of Topehaehae gley soil and Kereone sandy loam. Simulated farm dairy effluent, containing laboratory grown Escherichia coli O157:H7 and Campylobacter, was added to cores and turfs that were stored at 10°C. Bacterial survival was measured in cores over 28 days. Simulated rainfall was applied at 25 and 50 mm h -1 to allow measurement of bacterial transfer to drainage (over 28 days) or surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…PFGE was used in this study to explore the genetic diversity of E. coli O26 isolates and their spatial separation or relatedness from separate farms. Water may represent an important transmission source for a number of zoonotic pathogens including STEC which have previously been isolated from various water sources in New Zealand [39]. Although our study did not have the power to explore the population structure of STEC between farms in detail, our data are consistent with a previous molecular epidemiological investigation of 163 STEC O157 isolates that indicated isolates from the same farms had similar molecular profiles compared to isolates from different farms indicating limited transmission of STEC O157 between farms [40].…”
Section: Discussionmentioning
confidence: 99%
“…PFGE was used in this study to explore the genetic diversity of E. coli O26 isolates and their spatial separation or relatedness from separate farms. Water may represent an important transmission source for a number of zoonotic pathogens including STEC which have previously been isolated from various water sources in New Zealand [39]. Although our study did not have the power to explore the population structure of STEC between farms in detail, our data are consistent with a previous molecular epidemiological investigation of 163 STEC O157 isolates that indicated isolates from the same farms had similar molecular profiles compared to isolates from different farms indicating limited transmission of STEC O157 between farms [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, environmental sources, such as water used for recreational purposes and stormwater flows, represent an often overlooked source of disease transmission (Adak et al, 1995 ; Pond, 2005 ; Arnone and Walling, 2007 ); 3% of confirmed cases in the UK were reported as the direct result of contact with contaminated water supplies (Anonymous, 2000 ). Campylobacter survival within non-biological settings (i.e., water and soils) (Thomas et al, 1999 ; Ross and Donnison, 2006 ; Donnison and Ross, 2009 ; Rodríguez and Araujo, 2012 ), is dependent on numerous exogenous variables. Sensitivities to seasonal variations, temperature, sunlight exposure and dissolved nutrients have been observed to directly affect concentrations of the bacterium within water sources (Jones, 2001 ; Boyle et al, 2008 ; Maal-Bared et al, 2012 ; Rodríguez and Araujo, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…3a and 4, Chandrasekaran et al, 2015). Intense precipitation increases surface runoff and enhanced transport of indicator bacteria from pasture to streams (Castillo et al, 2004;Donnison and Ross, 2009;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%